Health risks associated with radon concentrations in carbonate and evaporite sequences of the uranium-rich district Karak, Pakistan - Khan, Mumtaz Ali; Khattak, Nimat Ullah; Hanif, Muhammad; Al-Ansari, Nadhir; Khan, Muhammad Bashir; Ehsan, Muhsan; Elbeltagi, Ahmed (Frontiers in Environmental Science, 2022)
The present research was carried out to investigate the behavior of radon (222Rn) concentrations over the carbonate and evaporite sequences and to assess the related health hazards. A total of 50 points from three different stratigraphic units, namely, the Bahadurkhel Salt, Jatta Gypsum, and the Kohat Formation of the Eocene age, were analyzed for radon concentrations in the district of Karak, Khyber Pakhtunkhwa, Pakistan. Measurements for radon levels were made by using RAD7 of Durridge, United States. The highest average 222Rn concentration (16.5 Bq/L) was found in the limestone unit of the Kohat Formation of the Eocene age. However, the lowest radon levels were observed in the salt-bearing strata of the Bahadurkhel Salt of the Eocene age. The study revealed that the average radon concentration in all the lithologies varied in the order of RnLimestone > RnSalt > RnGypsum. The findings of the current research suggest that the study area is safe from radon-related health hazards.